Association of Ankle-Brachial Index with the Angiographic Severity of Patient with Coronary Artery Disease (Cardiovascular Journal, 2018)
Background: The Ankle-Brachial Index has been shown to be a good marker of systemic atherosclerosis and a powerful indicator of cardiovascular morbidity and mortality This study evaluated the relation of ABI with the angiographic severity of patient with coronary artery disease.Methods: This is a hospital based cross-sectional analytical study. 100 adult Bangladeshi patients who were admitted and underwent coronary angiography according to inclusion and exclusion criteria were the study population. All patient’s ABI were measured and coronary angiography were done. Patients were divided into two groups according to ABI. Group I with ABI >0.90 and group II with ABI